Penerapan Pijat Oksitosin dan Marmet untuk Meningkatkan Produksi ASI Ibu Nifas - Ibrahim, Fatmawati (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2020)
Breastmilk is needed by babies because of its vitamins that are needed for the growth of the baby's brain which is undergoing rapid development from the age of 0-6 months to the age of 2 years, what if the baby is malnourished then the cells in the baby will shrink to 15% up to 20%, Unfortunately, many postpartum mothers cannot express breast milk properly and smoothly. Breastfeeding is a very closely related interaction between mechanical, nervous, and hormonal stimuli that affect the release of oxytocin. This study aims to determine the effect of oxytocin massage and market technique on breast milk production in postpartum mothers. This research uses a quasi-experimental design, with pre and post-test design. The number of samples was 20 respondents with purposive sampling. Data analysis in this study